Survei Kuantitatif Kepuasan Pemirsa terhadap Pelayanan Informasi dan Program Lokal TVRI Sulawesi Selatan - Arienda, Hanun Dzikra; Sonni, Alem Febri; Akbar, Muh. (Universitas Muhammdiyah Yogyakarta, 2025)
This study analyzes viewer satisfaction with the information services and local programs of TVRI South Sulawesi. Using a descriptive quantitative survey, data were collected through an online questionnaire completed by 260 viewers, mostly from younger age groups. The results show a high level of satisfaction with program content, presentation, and several technical aspects of the broadcast. Viewers particularly appreciate the themes and messages of local programs, the attractive presentation, competent hosts, and suitable broadcast schedules. However, concerns remain regarding technical quality, especially signal stability and studio lighting, which require improvement. The study recommends strengthening digital broadcast infrastructure and continuing to innovate program formats and presentation styles to better meet audience expectations. These findings are expected to support TVRI South Sulawesi in improving service and programming quality and to provide a reference for other local television stations.